KETERAMPILAN MAHASISWA PGMI DALAM MELAKSANAKAN PRATIKUM DENGAN MENGGUNAKAN KOMPONEN INSTRUMEN TERPADU (KIT) IPA - Gusti Handayani (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2019)
Science is the one of the discipline which probes the complex natural phenomena, that the learning should facilitate with the certain tools to aid students to understand its complexity. One of the solution to help Science is integrated component instrument (KIT). The research is done to notice the students’ skill in doing their experiment by using KIT. The sample were 30 students of PGMI. The instrument used in this research observation sheets and questionnaire that had been set based on certain aspects. Overall, the questionnaire result was 72% which categorized as good. The observation reported if generally the student’ skill in KIT activity got 64% or characterized by fair place. At last, the highest scores was obtained in attitude aspect either through questionnaire or observation.